Dermoscopy in Merkel Cell Carcinoma: A Case Report - Guiote Domínguez, Victoria (2018)
Merkel cell carcinoma is a rare neuroendocrine tumor localized in photo-exposed areas in aged adults. A high risk of local recurrence, early metastatic disease and, frequently, a late diagnosis, are determinant of a poor prognosis. Dermoscopic examination of this lesion, which is characterized by the presence of multiple atypical vessels and “red-milky areas”, might be a very useful tool to suspect the diagnosis rapidly and early, allowing treatment in due time. The authors report the case of a 71-years-old patient presenting with a Merkel cell carcinoma in the right lower limb in which the dermoscopic findings picked up a high grade of suspicion and allowed tumor excision in a clinically useful and treatable time. The authors also describe the most important dermoscopic findings and patternsobserved in this tumor and the differential diagnosis one must consider in these cases.